Fundamentals of Bone Degradation Chemistry: Collagen is Not "The Way". Issue 3 (18th July 2016) - Gillespie, Richard
Abstract : Collagen-based pretreatment methods for bone yield inconsistent results for those samples where protein preservation is low, as frequently found in bones from the semi-arid zones of Australia and North America. New methods for dealing with low collagen bones are needed, and this paper suggests that the non-collagenous proteins, particularly the blood proteins, may offer advantages for AMS dating because of their better preservation. Amino-acid profiles of collagen and non-collagenous proteins suggest that such differential preservation may be due to physico-chemical differences, and help to explain the poor results from dating low-collagen bones.